2013
DOI: 10.1111/jdi.12088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of periodontal treatment on glycemic control of patients with diabetes: A systematic review and meta‐analysis

Abstract: Aims/Introduction: The aim of the present study was to investigate whether non-surgical periodontal treatment reduces glycated hemoglobin (HbA 1c ) and fasting plasma glucose (FPG) levels in diabetic patients. Materials and Methods: An electronic search was carried out on MEDLINE (through PubMed interface), EMBASE and the Cochrane Central Register of Controlled Trials. Randomized controlled trials with a minimum of 3 months follow up were included. The risk of bias was assessed for each study. A meta-analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 49 publications
4
57
1
3
Order By: Relevance
“…Our results showed a mean reduction in Hb1Ac over time (0-3) and a tendency to decrease in the following quarter, similar to findings obtained from a systematic review [20], where similar results were demonstrated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results showed a mean reduction in Hb1Ac over time (0-3) and a tendency to decrease in the following quarter, similar to findings obtained from a systematic review [20], where similar results were demonstrated.…”
Section: Discussionsupporting
confidence: 91%
“…Since the 1960s, studies have been conducted with the aim of demonstrating the possible benefits of periodontal therapy in the glycemic control of diabetic patients [20], where surgical and non-surgical periodontal therapies may be able to reduce the systemic inflammatory gradient, thus favoring glycemic control although this fact is not yet a consensus in literature due to the lack of more homogenous and well delineated studies [5,7,12,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Nonsurgical periodontal therapy (such as plaque and calculus debridement using ultrasonic hand instruments) contributes toward minimizing oral soft tissue inflammation. [24][25][26] The biannual visits to oral healthcare providers may also have encouraged the participants in both groups to routinely maintain their oral hygiene status. It is therefore likely that regular oral hygiene maintenance contributed toward maintaining a healthy peri-implant soft tissue status and minimizing ABR around short implants in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…& Chronic periodontal inflammation may increase the risk for type 2 diabetes [41••, 42-46, 47•]. & Although the predominance of evidence suggests that treatment of periodontal disease may improve glycemic control, this is inconclusive [48][49][50][51][52][53][54][55][56][57]. However, a recent Cochrane Review concluded that there is insufficient evidence that improvement in glycemic control can be maintained after 4 months following treatment using nonsurgical treatment modalities [58•].…”
Section: Evidence On the Interrelationship Between Diabetes And Periomentioning
confidence: 98%